BIODIVERSITY CONSERVATION EFFORTS AMONG MUSLIM COUNTRIES: EVIDENCE FROM THE ORGANIZATION OF ISLAMIC COOPERATION COUNTRIES (Journal of International Studies, 2024)
According to mainstream literature, Muslim countries often lag behind in terms of environmental sustainability despite their beingfully compliant with global environmental regulations. This raises the question of whether this applies to all aspects of environmentalconservation. Therefore, this paper aims to evaluate the effectiveness of biodiversity conservation efforts in countries that are members of the Organization of Islamic Cooperation (OIC) and determine whether a consistent growth trend in biodiversity conservation can be identified. The study employs semi-quantitative and policy-science methods, analysing data from Yale University’s Biodiversity and Habitat Protection Index from 2010 to 2020. The findings show a significant increase in biodiversity conservation performance over the ten-year study period. Interestingly, low-income countries outperformed their wealthier OIC counterparts in terms of biodiversity conservation, despite having the lowest economic development status. This positive trend highlights the effectiveness of essential biodiversity policies and measures adopted in these Muslim countries. Furthermore, these results align with Stern’s approach, which argues that economic expansion can have diverse impacts on environmental quality, leading to the rejection of the Environmental Kuznets Curve hypothesis in the context of biodiversity conservation in Muslim countries. The study emphasises the need for further research into the nature of biodiversity policies among low-income nations. The policy ideas and solutions from these countries can provide valuable insights for combating biodiversity loss within OIC countries and globally, contributing to achieving Sustainable Development Goals (SDGs). Additionally, it has the potential to enhance the capacity of OIC countries in biodiversity conservation and their role in supporting fellow Muslim nations in achieving the SDGs.